Does First Nations ancestry modify the association between gestational diabetes and subsequent diabetes: a historical prospective cohort study among women in Manitoba, Canada. Issue 9 (3rd November 2015) - Shen, G. X.; Shafer, L. A.; Martens, P. J.; Sellers, E.; Torshizi, A. A.; Ludwig, S.; Phillips‐Beck, W.; Heaman, M.; Prior, H. J.; McGavock, J.; Morris, M.; Dart, A. B.; et al.
Abstract: Background: Over the past 30 years, the prevalence of diabetes has steadily increased among Canadians, and is particularly evident among First Nations (FN) women. The interplay between FN ancestry, gestational diabetes and the development of subsequent diabetes among mothers remains unclear. Methods: After excluding known pre‐existing diabetes, we explored whether FN ancestry may modify the association between gestational diabetes and post‐partum diabetes among women in Manitoba (1981–2011) via a historical prospective cohort database study. We analysed administrative data in the Population Health Research Data Repository using Kaplan–Meier survival analysis and Cox proportional hazards regression. Results: Gestational diabetes was diagnosed in 11 906 of 404 736 deliveries (2.9%), 6.7% of FN and 2.2% of non‐FN pregnant women ( P < 0.0001). Post‐partum diabetes during ≤ 30 years follow‐up was more than three times higher among FN women than among non‐FN women ( P < 0.0001). Diabetes developed in 76.0% of FN and 56.2% of non‐FN women with gestational diabetes within the follow‐up period. The hazard ratio of gestational diabetes for post‐partum diabetes was 10.6 among non‐FN women and 5.4 among FN women. Other factors associated with a higher risk of diabetes included lower family income among FN and non‐FN women and rural/remote residences among FN women. Among non‐FN women, urban residence was associated with a higher risk of diabetes. Conclusion: Gestational diabetes increases post‐partum diabetes in FN and non‐FN women. FN women had substantially more gestational diabetes or post‐partum diabetes than non‐FN women, partially due to socio‐economic and environmental barriers. Reductions in gestational diabetes and socio‐economic inequalities are required to prevent diabetes in women, particularly in FN population. What's new?: This historical cohort study examined the impact of gestational diabetes after excluding pre‐existing diabetes in mothers who delivered between 1981 and 2011 in Manitoba, Canada. First Nations (FN) women had two times more gestational diabetes and were three times more likely to develop post‐partum diabetes than non‐FN women. Post‐partum diabetes in both FN and non‐FN mothers was affected by gestational diabetes, lower family income and rural residence. The relative risk of developing post‐partum diabetes in non‐FN women was higher than in FN women. The findings suggest that reductions in gestational diabetes and socio‐economic inequities are required to prevent post‐partum diabetes in FN and non‐FN women.